Perubahan Konteks Pariwisata dalam Komodifikasi Tradisi Mekotek pada Masa Pandemi Covid-19 - Purnawan, I Nyoman Aris; Erviantono, Tedi; J. M., A.A.S. Mirah Mahaswari (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This study aims to determine the changes in the tourism context in the commodification of the mekotek tradition into fragments of the mekotek dance in the Munggu Traditional Village. The theory of the determining elite by Keller is used to analyze the determining elite in the change of the mekotek tradition into fragments of the mekotek dance. By using qualitative methods through interviews with the Bendesa Adat Munggu, Perbekel Desa Munggu, and Pokdarwis Desa Adat Munggu, the results of the research are as follows: First, the sacred tradition of mekotek is commodified into fragments of mekotek dance so that it can be sold to tourists. Second, the mekotek dance fragment was initiated and fully managed by the Tourism Awareness Group (Pokdarwis) of the Munggu Traditional Village. And third, the income from the mekotek dance fragment is managed by Pokdarwis and then handed over to the BumDes of Munggu Traditional Village.